The Research Progress of Antiangiogenic Therapy, Immune Therapy and Tumor Microenvironment - Hu, Haoyue; Chen, Yue; Tan, Songtao; Wu, Silin; Huang, Yan; Fu, Shengya; Luo, Feng; He, Jun (Frontiers in Immunology, 2022)
Anti-angiogenesis therapy is a promising strategy against cancer progression but is limited by drug-resistance, which could be attributed to the changes in the tumor microenvironment. Studies increasingly show that combining anti-angiogenesis drugs with immunotherapy synergistically inhibits tumor growth and progression. In this review, the current anti-angiogenesis therapies and corresponding drug-resistance, the relationship between tumor microenvironment and immunotherapy, and the latest progress on the combination of both therapeutic modalities have been discussed. The aim of this review is to summarize the combination of anti-angiogenesis therapy with immunotherapy can exert synergistic antitumor effect, which provides a basis for exploring new targets and developing more advanced strategies.